Analisis Interaksi Sosial Facebook Pada Grub Keluh Kesah Ngampus (KKN) - Witnes Madinatul Mi’roj; Qoni'ah Nur Wijayani (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The Facebook group "Complaints about Missing Campus" is an online forum that allows students to share experiences, concerns and stories about their university life. The aim of this research is to analyze the social interactions that occur within this group, as well as to understand how this group plays a role in meeting the social needs of its members. This study uses content analysis methods and online observation to collect data from posts, comments and interactions between members in the "Complaints about Ngampus" group. The results of the analysis show that this group is a significant platform for members to share their feelings, experiences and suggestions regarding study issues, campus life and other social aspects. Social interactions within this group reflect multiple types of social support, including emotional, informational, and evaluative support. Members share their stories, offer advice, and provide moral support to each other. These groups also facilitate the formation of social bonds and friendships among their members. The Facebook group "Complaints about Dismissals" can serve as a safe place to express discomfort, pursue solutions together, and build a supportive social network among college students. Social interaction in this group plays an important role in overcoming the challenges of college and campus life, and helps improve the social and emotional well-being of its members.